Damage from dissection is associated with reduced neuro-musclar transmission and gap junction coupling between circular muscle cells of guinea pig ileum, in vitro - Carbone, Simona E.; Wattchow, David A.; Spencer, Nick J.; Hibberd, Timothy J.; Brookes, Simon J. H. (Frontiers in Physiology, 2014)
Excitatory and inhibitory junction potentials of circular smooth muscle cells in guinea pig ileum and colon are suppressed 30-90 minutes after setting up in vitro preparations. We have previously shown this ‘unresponsive’ period is associated with a transient loss of dye coupling between smooth muscle cells, which subsequently recovers over the ensuing 30-90 minutes; junction potentials recover in parallel with dye coupling (Carbone et al., 2012). Here, we investigated which components of dissection trigger the initial loss of coupling. Intracellular recordings were made from circular muscle cells of guinea pig ileum with micropipettes containing 5% carboxyfluorescein. After allowing 90-120 minutes for junction potentials to reach full amplitude, we re-cut all 4 edges of the preparation more than 1mm from the recording sites. This caused a reduction in the amplitude of IJPs from 17.2± 0.7mV to 9.5±1.5mV (P<0.001, n=12) and a significant reduction in dye coupling. Both recovered within 60 minutes. We repeated this experiment (n=4), recording both 1mm and 4mm from the cut edge: both sites were equally affected by re-cutting the sides of the preparation. Equilibrated preparations were stretched to 150% of their original length, this had no significant effect on junction potentials or dye coupling. Setting up preparations in low calcium solution did not prevent the initial suppression of IJPs and dye coupling. Application of 3µM indomethacin (n=3), 10µM ketotifen (n=4) or 10µM forskolin during dissection did not prevent the suppression of IJPs and dye coupling. If dissection damage was reduced, by leaving the mucosa and submucosa attached to the circular muscle, IJPs showed less initial suppression than in preparations where the layers were dissected off. We conclude that physical damage to the gut wall triggers loss of gap junction coupling and neuromuscular transmission, this is not due to stretch, influx of calcium ions, release of prostaglandins or mast cell.